75th anniversary of Doctor of Physical and Mathematical Sciences, Professor M.T. Jenaliyev - Ramazanov , M.I. (Bulletin of the Karaganda University. Mathematics Series, 2022)
On January 25, 2022, a well-known specialist in the field of the theory of partial differential equations and its applications, Chief Researcher of the Institute of Mathematics and Mathematical Modeling of the Committee of Science of the Ministry of Education and Science of the Republic of Kazakhstan, Doctor of Physical and Mathematical Sciences, Professor Muvasharkhan Tanabaevich Jenaliyev, turned 75 years old.